A Model for Professional Development and School Improvement in Rural Schools - Dianne A. Seltzer (Journal of Research in Rural Education, 1995)
The model we describe below provides aframeworkfor rural educators to employ as they seek ways to improve their schools and meet the national goal ofproviding all teachers access to professional development opportunities. Implementation strategies of our model include commitment ofschool teams; assistance based on the teams' assessment oftheir needs; a focus on teaching and learning strategies that promote meaningful connections; extended planning time for teams; recognition that change is a long-term process that requires long-term support; networking of teams across schools to promote collegial support; ownership of the professional development agenda; and process evaluations to guide future professional development opportunities.